Shelf Life and Secondary Metabolite Content of Sweet Potato (Ipomoea batatas L.) Lam. Coated with Chitosan Coating at Low Temperature Storage - Widya Mudyantini; Suranto Suranto; Solichatun Solichatun; Nita Etikawati; Ari Pitoyo; Suratman Suratman; Tanjung Ardo (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2023)
Sweet potato (Ipomoea batatas (L.) Lam.) has diverse varieties with different secondary metabolite content. Postharvest treatment with low-temperature storage and chitosan coating is expected to expand the shelf life of sweet potatoes. The combination of these treatments will affect the secondary metabolite content of diverse sweet potato varieties. Therefore, this study aims to observe the secondary metabolite content and shelf life extension of 3 sweet potato varieties after coating with chitosan and low-temperature storage. A completely randomized design (CRD) was used with a three-factors experiment. The first factor was chitosan concentration at 0, 10, 15, and 20 g/L, the second was storage room temperature at 25, 15, and 5 °C, while the third was the color of sweet potato varieties namely white, purple, and orange from Tembakur and Mendut varieties. Meanwhile, the control group was tubers without chitosan coating at a storage temperature of 25 °C. Each treatment had five replications and the parameters assessed were changes in wet weight, hardness, respiration, the total chlorophyll level, carotenoid, vitamin C, reducing sugar, and the level of flavonoid. Data were analyzed with Analysis of Variance and then continued with Duncan's Multiple Range Test at a significance level of 5%. The result showed that low-temperature storage combined with chitosan coating affected the shelf life of sweet potatoes. Overall, the best storage temperature was 15 °C, indicated by the highest residual secondary metabolite and the most extended shelf life. The 5°C treatment decreased oxygen consumption during storage, as indicated by a low respiration rate. However, this storage temperature caused a chilling injury and culminated in the shorter shelf life of all examined sweet potatoes. The best coating was achieved by chitosan 15 g/L, indicated by the capability to coat sweet potato surface and maintain the high content of all targeted chemical components. The results also revealed that 20 g/L chitosan concentration is not practical for coating due to its in elasticity and the potential to create a crack in the coating layer.